The Strategic Importance of M&A in the Biotech and Pharmaceutical Industry - Desai, Savri (2011)
Background: The companies involved for the purpose of improving their respective market standings and income executes mergers. It is interesting how this merger & acquisition phenomena continue to attract many organizations across different sectors of the business world. The mergers & acquisition culture around the globe provides an ideal scenario to investigate into the healthcare industry which comprises of pharmaceutical and biotech companies and the impact of the mergers on the firms involved. This study seeks to explore the motives behind takeovers and also the most suitable form of organizational integration in great detail.